2010
DOI: 10.1007/s10519-010-9356-y
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment, MAOA, and Delinquency: Sex Differences in Gene–Environment Interaction in a Large Population-Based Cohort of Adolescents

Abstract: The present study investigated a possible interaction between a functional polymorphism in the MAOA gene promoter (MAOA-VNTR) and childhood maltreatment in the prediction of adolescent male and female delinquency. A cohort of 1,825 high school students, 17-18 years old, completed an anonymous questionnaire during class hours which included questions on childhood maltreatment, sexual abuse, and delinquency. Saliva samples were collected for DNA isolation, and analyzed for the MAOA-VNTR polymorphism. Self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 54 publications
14
90
3
1
Order By: Relevance
“…Findings in the opposite direction in the ACC during a flanker NoGo task suggested that increased emotional activity coincided with decreased inhibitory control. This finding is in line with previous studies reporting a sex-specific effect of MAOA on aggression (Byrd and Manuck 2014;Aslund et al 2011), which is likely due to the X-linked locus of the MAOA gene resulting in two copies in females and one copy in males.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings in the opposite direction in the ACC during a flanker NoGo task suggested that increased emotional activity coincided with decreased inhibitory control. This finding is in line with previous studies reporting a sex-specific effect of MAOA on aggression (Byrd and Manuck 2014;Aslund et al 2011), which is likely due to the X-linked locus of the MAOA gene resulting in two copies in females and one copy in males.…”
Section: Discussionsupporting
confidence: 93%
“…In female subjects, findings suggested differential interaction patterns. Some studies reported an interaction of the high-expressing variant MAOA-H with early environmental adversity predicting the development of aggressive or antisocial behavior (Aslund et al 2011;Sjoberg et al 2007;Prom-Wormley et al 2009), while others confirmed MAOA-L as the risk allele in the interaction (Ducci et al 2008;Widom and Brzustowicz 2006) or reported no interaction at all (Frazzetto et al 2007). A potential sex dependence of the MAOA by environmental adversity could partly be explained by the X-linked transmission of the gene, resulting in females carrying two copies and males only one copy.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Aslund et al (2011) and Nilsson et al (2011) (Table 1) examining, respectively, delinquent behaviour and high alcohol consumption. MAOA polymorphism was also found to enhance depressive symptoms but only among extensively maltreated youth (i.e.…”
Section: -25supporting
confidence: 86%
“…In contrast, more inconsistency has been observed with regard to gender. While several studies replicated the original G 9 E in females (e.g., Weder et al 2009), others reported effects in the reverse direction, with the high activity allele conferring risk of violent behavior in females exposed to maltreatment (e.g., Aslund et al 2011), and others still found no interaction at all (e.g., Frazzetto et al 2007). As a potential source of heterogeneity, differences in MAOA expression between males and females have been discussed.…”
Section: Molecular Genetic Studies Of G Ementioning
confidence: 91%
“…A number of investigations confirmed the interaction between MAOA genotype and child maltreatment with regard to antisocial behavior in studies of maltreated children (e.g., Weder et al 2009), adolescents (e.g., Aslund et al 2011), and adults (e.g., Ducci et al 2008). In contrast, more inconsistency has been observed with regard to gender.…”
Section: Molecular Genetic Studies Of G Ementioning
confidence: 96%